Particular features of labor activity at the presence of inflammation of the uterine layers and placental membranes - K.L. Shatylovych; L.B. Markin (Publishing House TRILIST, 2023)
Research objectives: to analyze the association between the various abnormalities of the labor activity and inflammatory changes of the placental, fetal membranes, and uterine layers. Materials and methods. A prospective cohort study of 382 patients with singleton pregnancies at 28-42 weeks' gestation who underwent cesarean section for abnormal uterine contractions and other complications was conducted. The patients were divided into 3 observation groups: 168 women with hypotonic labor (HL), 70 women with hypertonic uterine dysfunction (HUD) and 144 women operated on for various indications (control group). The development of the inflammation of the decidua, myometrium, chorioamniotic membranes and umbilical cord in different types of labor activity abnormalities were studied. Statistical analyses included Mann-Whitney U test, Chi-squared test, and logistic regression. Results. In the control group on the eve of the labor the lower uterine segments' polymorphonuclear leukocytes and macrophages infiltration of mild grade were detected in 73.6 and 59.7% cases accordingly. The strength of the association of uterine layers, placental and fetal membranes inflammation with the HUD was: for the deciduitis - adjusted odds ratio (aOR): 2.6, 95% confidence interval (CI): 1.4-4.8; for the myometritis - aOR: 0.7, 95% CI: 0.3-2.4; for the histological chorioamnionitis (hCAM) - aOR: 4.5, 95% CI: 3.4-12.1; for the funisitis - aOR: 2.9, 95% CI: 1.3-10.6. The main clinical risk factors for hCAM, funisitis, and deciduitis in the HUD group, such as prematurity, nulliparity, group B streptococcus colonization, and duration of ruptured fetal membranes before the cesarean section, indicated the antenatal occurrence of inflammatory process. А decrease of the uterine contractility іn the HL group was associated with grade 2+ deciduitis (aOR: 1.4, 95% CI: 0.6-3.6) and grade II+ myometritis (aOR: 3.9, 95% CI: 1.3-14.7), but no association was found with stage II+ hCAM (aOR: 0.8, 95% CI: 0.3-4.9) and stage 2+ funisitis (aOR: 0.3, 95% CI: 0.6-2.7). Decidual and myometrial inflammation was significantly connected with nulliparity and intrapartum factors such as protracted active first stage of labor with oxytocin augmentation, advanced cervical dilation, and number of vaginal examinations. Inflammation of the myometrium was accompanied by the deciduitis in all cases. Conclusions. Mild inflammation of the decidua and myometrium of the lower segment of the uterus at term pregnancy is a physiological phenomenon that contributes to the initiation of labor. Inflammation of the chorioamniotic membranes and decidua against the background of intact myometrium plays a fundamental role in the occurrence of hypertensive uterine dysfunction, particularly in preterm birth. Marked myometrial inflammation that occurs in prolonged labor is an additional factor aggravating the hypotonic uterine activity.